Estudo comparativo das tensões na interface de compósitos de resina epóxi reforçados com fibras de carbono, aramida e vidro. - Nossa, Tamires de Souza (2011)
Currently, composite materials are being used in several areas in substitution of some metallic alloys regarding to its superior properties and greater project flexibility. Therefore, synthetic fibers reinforced epoxy resin has some mechanical properties limited by its interface due to the interaction between fiber and matrix. The present research studies the interaction between the materials at the interface, considering the resin interaction with the three most employed composites fiber: carbon fiber, Aramida (Kevlar) and glass fiber (E type). The fibers surfaces were analyzed through the AFM (atomic force microscope) and the Contact Angle Method (CAM), becoming possible to determine the surface energy of each material, the superficial interface energy, the matrix-fiber adhesion and the surface profile analysis. The composites were subjected to the single fiber fragmentation test (SFFT) in order to obtain its interfacial share strength to be applied in the Kelly-Tyson equation. Furthermore, through these analysis became possible to evidence the properties differences between the composites, the individual properties of matrix-fiber that can be obtained, the best matrix-fiber interface, classifying them according to the stress transference magnitude and, consequently, greater effectiveness on the matrix-fiber adhesion.